A cross-sectional study on the etiological spectrum and morbidity profile among geriatric patients: A hospital-based study - Tiash Samanta,; Satyendra Nath Saha,; Moumita Sen,; Chaudhuri, Arunima; Badal Kumar Sahu, (Asian Journal of Medical Sciences, 2024)
Background: Elderly people are now the most rapidly growing population group worldwide, and the challenge ahead for the health-care system is to ensure the quality of life and provide adequate health care for a large group the of geriatric population. Aims and Objectives: The objective of the study was to determine the most common causes of emergency hospital admission of geriatric patients and to evaluate their morbidity profile. Materials and Methods: This present study was carried out on 208 geriatric patients (age >60 years) in a medical college and teaching hospital, in eastern India between May 2019 and October 2020 after taking institutional ethical clearance and informed consent of the participants. Results: Nearly 38.9% of the participants belonged to the age group of 60–70 years. 73.7% of the participants presented with respiratory diseases (chronic obstructive pulmonary disease and respiratory failure), 21.0% had pulmonary tuberculosis, and 5.3% had cancer lung. Nearly 88.46% had endocrinal morbidity, followed by cardiovascular morbidity (74.03%) and respiratory morbidity (62.50%). 81.25% of the participants had diabetes, and 60.58% suffered from musculoskeletal disorder. 36.53% had osteoarthritis and 22.59% had rheumatoid arthritis. Conclusion: The present study result showed the most common presentation in hospital admissions during the emergency in the elderly were cardiovascular, respiratory diseases, neurological causes, and gastrointestinal disorders. The majority of cases had three or more complications necessitating admission contributing to a higher disease burden in the elderly.